Fake news falsehood, fabrication and fantasy in journalism - McNair, Brian 1959- (Disruptions: studies in digital journalism, 2018)
"Fake News: Falsehood, fabrication and fantasy in journalism examines the causes and consequences of the 'fake news' phenomenon now sweeping the world's media and political debates. Drawing on three decades of research and writing on journalism and news media, leading scholar Brian McNair engages with the fake news phenomenon in accessible, insightful language designed to bring clarity and context to a complex and fast-moving debate. McNair presents fake news not as a cultural issue in isolation but rather as arising from, and contributing to, significant political and social trends in twenty-first century societies. Chapters identify the factors which have laid the groundwork for fake news' explosive appearance at this moment in our globalised public sphere. These include the rise of relativism and the crisis of objectivity, the role of digital media platforms in the production and consumption of news, and the growing drive to produce online content which attracts users and generates revenue. The book also considers the decline of trust in journalism, and the how the traditional left critique of 'dominant ideology' and 'ruling elites' in media has been appropriated by the alt-right, nationalists and populists all over the world.This book rejects the left-right division in discussion of what is and is not 'fake news'. Rather, it aims to provide students, teachers, journalists and general readers with the tools necessary to navigate the digital journalism landscape in the era of President Donald Trump, and to filter out the 'fact' from the 'fake' in their news."--Provided by publisher.